A computational study of nonresonant cross-field diffusion of energetic particles due to their interaction with interplanetary magnetic decreases - Costa Jr., E.; Echer, E.; Alves, M.V.; Tsurutani, B. T.; Simes, F. J. R.; Cardoso, F. R.; Lakhina, G. S. (My University, 2011)
We present a new method of calculating cross-field diffusion of charged particles due to their interactions with interplanetary magnetic decreases (MDs) in high heliospheric latitudes. We use a geometric model that evaluates perpendicular diffusion to the ambient magnetic field as a function of particle's gyroradius, MD radius, ratio between fields outside and inside the MD, and a random impact parameter. We use Ulysses magnetic field data of 1994 to identify the MDs and get the empirical size and magnetic field decrease distribution functions. We let protons with energies ranging from 100 keV to 2 MeV interact with MDs. The MD characteristics are taken from the observational distribution functions using the Monte Carlo method. Calculations show that the increase in diffusion tends to saturate when particles' gyroradius becomes as large as MD radii, and that particles' gyroradius increases faster than diffusion distance as the energy of the particles is increased.
Keywords: Magnetic decreases; Particles diffusion; Nonresonant interactions; Monte Carlo simulation